How to foster climate innovation in the European Union: Insights from the EIB Online Survey on Climate Innovation - Julie Delanote; Désirée Rückert (European Investment Bank (EIB), 2022)
Using survey data on climate innovation, we map climate innovation patterns across different regions and technologies, and study the cooperation, protection and reach of climate innovation. Our analysis confirms that there is a strong link between climate innovation and firm performance. We nevertheless observe that European firms seem to suffer from the availability of finance. If European policymakers want to create more successful firms in the climate sector, they should strengthen policies that aim to reduce regulatory uncertainty and work actively to improve access-to finance conditions, in particular for start-ups.
Keywords: 330; Climate action and environment; Economics